The Estimation of Frictional Unemployment: A Stochastic Frontier Approach - Warren, Ronald S. (The Review of Economics and Statistics, 1991)
This paper reports an estimate of the frictional unemployment rate in U.S. manufacturing that is derived from a parametric, statistical method for estimating stochastic frontiers. The steady-state, perfect-foresight solution to an estimated employment growth frontier provides a locus of technically efficient (frictional) rates of unemployment. The mean frictional unemployment rate during the sample period is estimated to be 3.7 percent of the manufacturing labor force. This estimate conforms closely to an estimate of 3.5 percent that is derived from manufacturing-sector data presented by David M. Lilien (1980) for roughly the same time period. Copyright 1991 by MIT Press.